Development of Arduino Assisted Microcontroller Instructional Devices in Vocational High Schools - Wijaya, H A; Khairudin, M (Journal of physics. Conference series, 2019)
This development research aims to find out: (1) feasibility, (2) functioning, and (3) the effectiveness of the arduino-assisted microcontroller assisted devices with the arduino simulator Xevro version 1.5 as a learning media for the material programming of microcontroller programming skills in Mechatronics Engineering at the Vocational High School. The subjects of this study were the XI grade students of the Mechatronics Engineering expertise program at vocational high schools N 1 Bawang Banjarnegara and Leonardo Klaten Vocational High School. The results of this study are an Arduino-assisted microcontroller simulation for microcontroller programming material. The results of the feasibility assessment of the Arduino-assisted microcontroller simulation according to the validator are 83.33 so that it is categorized as "Very Worthy" and according to students is 70.98 of a scale of 100 so that it is categorized as "Eligible". The results of the assessment of the function of Arduino-assisted microcontroller simulations according to the validator are 82.92 so that it is categorized as "Very Worthy" and according to students is 71.55 of a scale of 100 so it is categorized as "Eligible". This Arduino-assisted microcontroller simulation has an effective impact, because the significance value when tested using the t test is t count = 11.075> t table = 1.983 and Asymp. Sig (2-tailed) <0.05. The level of effectiveness can be seen from the magnitude of the gain value.